Carboplatin, paclitaxel, and pembrolizumab followed by pembrolizumab maintenance for primary treatment of incompletely resected epithelial ovarian cancer - Uyar, Denise; Michener, Chad M.; Bishop, Erin; Hopp, Elizabeth; Simpson, Pippa; Zhang, Liyun; Rader, Janet S.; Rose, Peter G.; Mahdi, Haider S.; Debernardo, Robert; Christian, Qiana; Bradley, William (Frontiers in Oncology, 2024)
Objective: Incompletely resected epithelial ovarian cancer represents a poor prognostic subset of patients. Novel treatment strategies are needed to improve outcomes for this population.We evaluated a treatment strategy combining platinum-based chemotherapy with pembrolizumab followed by pembrolizumab maintenance therapy in the first-line treatment after incomplete resection of epithelial ovarian cancer patients.Methods: Single arm, nonrandomized pilot study of carboplatin, taxane, and immune checkpoint inhibitor, pembrolizumab, followed by 12 months of maintenance pembrolizumab in patients with incompletely resected epithelial ovarian cancer (EOC).Results: Twenty-nine patients were enrolled and evaluated for efficacy and safety. The best response to therapy was complete response in 16 (55%) patients, partial response in 9 (31%) patients, and 3 (10%) patients with progression of disease. The median progression-free survival (PFS) was 13.2 months. Grade 3 and 4 toxicities occurred in 20% of patients. Seven patients discontinued therapy due to adverse events. Quality of life scores remained high during therapy. Response to therapy did not correlate with PD-L1 tumor expression.Combination platinum-taxane therapy with pembrolizumab did not increase median progression-free survival in this cohort of patients. Key Message: EOC is an immunogenic disease, but immune checkpoint inhibitor therapy has yet to impact outcomes. The current study utilizes pembrolizumab in combination with standard chemotherapy followed by a maintenance treatment strategy in incompletely resected EOC. Progression free survival was not extended in this poor prognostic group with combined chemotherapy and immunotherapy.